Optimalisasi Waktu Tunggu Antrian Bongkar Palm Kernel di Kernel Crushing Plant dengan Pendekatan Promodel - Sihotang, Helena; Dahlia, Savanna; Narendra, Sendi A; Setiawan, Andry (Greeners: Journal of Green Engineering for Sustainability, 2025)
Optimization is an effort to improve process outcomes in an ideal and effective manner. One approach to solving queuing system problems is through simulation. The Kernel Crushing Plant faces queuing issues due to uneven workload distribution among the sampling tower, laboratory, and weighbridge. This condition requires improvements to the queuing system model to achieve a more efficient process flow. Using Promodel software, the queuing system at the Kernel Crushing Plant can be virtually visualized by developing a new model. The proposed model includes separating palm kernel analysis from production analysis, implementing a robotic system for palm kernel sampling, and adding Foss NIRS equipment. The implementation of this model has been proven to reduce laboratory workload (percentage of operation) by nearly 23%, resulting in a more balanced productivity across all locations.